The Movement Order of Mahler’s Sixth Symphony: Musical Considerations - Niall O’Loughlin (Muzikološki Zbornik, 2008)
Mahler composed his Sixth Symphony with the Scherzo preceding the Andante, but reversed them before the first performance for all performances and published editions. However, some prominent musicians still insist on this order. With numerous thematic and harmonic connections between Alle- gro and Andante, and Scherzo and Finale, Mahler’s revised order is completely convincing.